Politics, Religion and the Song of Songs in Seventeenth-Century England - Clarke, E. author. aut Link
VIII, 265 p.
Keywords: The Song of Songs , with its highly sexual imagery, was very popular in seventeenth-century England in commentary and paraphrase. This book charts the fascination with the mystical marriage, its implication in the various political conflicts of the seventeenth century, and its appeal to seventeenth-century writers, particularly women.